AirAsia India 2017 - Dixit, Mukund R.; Jena, Sanjay Kumar (London : Indian Institute of Management, Ahmedabad, 2018)
The AirAsia India 2017 (AAI) case presents the situation faced by Tony Fernandes, the CEO of the AirAsia group of companies, in 2017, when he had to respond to the changes in aviation policy made by the Ministry of Civil Aviation (MCA). As per the changes, an airline operating in India could start its international operations without having five years of domestic flying experience provided it deployed 20 of its aircraft or 20% of the total capacity, whichever was higher, for domestic operations. Operating international flights was more lucrative than domestic routes as the price difference between domestic and international aviation turbine fuel was substantial. By July 2017, AAI had a fleet size of only eleven planes. If Fernandes decided to fly international, he had to buy another nine aircraft. Before that he had to turnaround AAI's domestic operations. The company was struggling to achieve its breakeven even after three years of domestic operations.
Originally Published InDixit, M. R., & Jena, S. K. (2018). AirAsia India 2017. IIMA/BP0422. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; AirAsia; Airplanes, Company -- India -- Management -- Case studies; Aeronautics, Commercial -- India